Minuman Alkohol dan Agama : Studi pada Remaja di Surabaya - Ferdi Gultom (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2022)
The practice of consuming alcohol has its own meaning for teenagers. Even though they understand and practice the rules of their religion, teenagers have their own knowledge about drinking alcohol. Through their knowledge, it is as if they can escape the rules of their religion. This study aims to identify the experience of consuming alcohol and adolescent religious practices in Surabaya. The study used qualitative research methods with a symbolic nonlism interaction theory approach to determine the perception of alcohol consumption; find out about alcohol consumption, thereby escaping religious rules. The results of this study indicate that adolescents have meanings about alcohol consumption, such as symbols of happiness, venting, breaking the atmosphere, gratitude, and togetherness. Teenagers give reasons that alcohol consumption is not a matter of halal or haram, as long as it does not harm others. The public stigma about alcohol is a social and religious deviation because it is used in a riot, to the detriment of others.